Restoring overlogged tropical forests - Sabogal, C.; Nasi, Robert (Springer, 2005)
Overlogged forests are degraded but nevertheless important. They may continue to be a source of timber and supply an important amount of forest products, particularly for local people who livelihoods depend on their extraction. One aspect of restoration would be to prevent adding more overlogged areas by implementing sound logging, silvicultural, and management practices. There is an urgent need to appropriately disseminate the existing strategies, approaches, and techniques that are most appropriate for forest restoration of overlogged forests.